Bioinformatics Toxicity Assessment of RB Protein from Transgenic Potato Resistant to Phytophthora infestans - Hadiarto, Toto; Ambarwati, Alberta Dinar (Makara Journal of Science, 2019)
The genetically engineered potato cultivar Katahdin SP951 is resistant to late blight disease, which is caused by Phytophthora infestans. The biosafety and food safety of this cultivar should be assessed prior to its commercialization. Toxicity is one of the parameters tested in the food safety evaluation of transgenics. Toxicity testing includes the bioinformatics analysis of the homology of the RB protein of Katahdin SP951 with known proteins. Therefore, this study aimed to perform the bioinformatics analysis of Katahdin SP951 RB protein against homologous toxin proteins. Bioinformatics analysis was conducted by first translating the RB gene into an amino acid sequence by using the Emboss Transeq program from the EMBL-EBI website. The Shuffle Protein Program was then applied to obtain the randomized amino acid sequences of the RB protein. The Basic Local Alignment Search Tool (BLAST) Protein search program was utilized to identify proteins with high similarity and homology. Moreover, BLAST Suite-2 was used to analyze the homology between two or more sequence alignments. Results showed high homology between the sequences of the RB protein and those of known resistance (R) proteins with an E value of less than 0.22. This result may be attributed to the presence of numerous R proteins in plants. Further analysis indicated that the sequence of the RB protein had extremely nonsignificant homology with sequences of proteins known to be toxic in the Entrez protein database of National Center for Biotechnology Information. Therefore, the RB protein is nontoxic.